Capital structure in Malaysia Government-Linked Companies (GLCs) / Erna Sharida Putek - Putek, Erna Sharida (2013)
Capital structure becomes the mainstream theme of corporate finance. The Modigliani-Miller known as MM theory define capital structure do not affects firms financing. There were three theory for capital structure, firstly static trade-off theory, pecking order theory and agency costs theory. Therefore, this study is designed to investigate which theories is the most dominant in Capital structure decision. Several factors such as firm size, profitability, liquidity and growth have been analysed. A set of panel data for a 6 year period (2006-2011), which consists of data from Government-Linked Companies (GLCs) has been used. Based on the Random Effects GLS Regression estimation, the results successfully highlight on the dominance of the firm size and growth. This is because large firm tend to be more diversified in their investment. Growth were significant because tend to borrow on short term basis. For future studies, it is proposed to have a lot of Government-Linked Companies to be analysis.